2022
DOI: 10.1002/pd.6128
|View full text |Cite
|
Sign up to set email alerts
|

Prenatally diagnosed isolated perimembranous ventricular septal defect: Genetic and clinical implications

Abstract: Objective To evaluate the incidence of chromosomal aberrations and the clinical outcomes following the prenatal diagnosis of isolated perimembranous ventricular septal defect (pVSD). Methods This retrospective study was composed of a cohort of pregnant women whose fetuses were diagnosed with isolated pVSD. Complete examinations of the fetal heart were performed, as well as a postnatal validation echocardiography follow‐up at 1 year of age. The collected data included: spontaneous closure of the pVSD, need for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In our series, the intrauterine natural closure rate of muscular VSDs was 40.0%, with that of perimembranous defects at 15.4%. Although previous studies reported that 27.3–54.1% of all prenatally detected perimembranous VSDs closed spontaneously in utero , these studies consisted of smaller cohorts ( 9 , 12 , 22 , 30 ). As reported in the literature, this high incidence of spontaneous closure of muscular VSD can be seen as a normal process of delayed, underlying physiological development, rather than an abnormality ( 34 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our series, the intrauterine natural closure rate of muscular VSDs was 40.0%, with that of perimembranous defects at 15.4%. Although previous studies reported that 27.3–54.1% of all prenatally detected perimembranous VSDs closed spontaneously in utero , these studies consisted of smaller cohorts ( 9 , 12 , 22 , 30 ). As reported in the literature, this high incidence of spontaneous closure of muscular VSD can be seen as a normal process of delayed, underlying physiological development, rather than an abnormality ( 34 ).…”
Section: Discussionmentioning
confidence: 96%
“…Remarkably, results varied widely, with reported detection rates of pathogenic CNVs ranging from 1.2 to 6.9%, including VSDs with differing definitions of “isolated” ( 16 21 ). In addition, subgroup analyses of different types of VSDs, the most typical structural abnormalities detected in the prenatal setting, are rarely reported ( 22 , 23 ). Therefore, the possible association between isolated VSD and the risk of chromosomal abnormalities, and whether the prenatal invasive procedure should be granted access to pregnant women when an isolated VSD has been detected in the prenatal setting, remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the small sample size, larger studies are still needed to further analyze the issue. A study showed that 45.4% of VSD closed in the womb, 30.9% closed in the rst year of life, and those with a defect larger than 3mm did not close spontaneously [15]. The average size of VSD in the operative and the non-operative groups was 3.89mm and 2.87mm, respectively (data not shown).…”
Section: Discussionmentioning
confidence: 96%
“…The frequency of associated genetic disorders for prenatally diagnosed perimembranous VSD depends on the presence of a first‐trimester screening. The risk of associated genetic disorders for fetuses with perimembranous VSD in the second trimester will be lower if fetuses with trisomies are diagnosed and terminated in the first trimester 13,14 . From a clinical perspective, prenatal detection of ventricular septal defects without a genetic disorder is less critical as it is often asymptomatic at birth, and there is no need for immediate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of associated genetic disorders for fetuses with perimembranous VSD in the second trimester will be lower if fetuses with trisomies are diagnosed and terminated in the first trimester. 13,14 From a clinical perspective, prenatal detection of ventricular septal defects without a genetic disorder is less critical as it is often asymptomatic at birth, and there is no need for immediate treatment. Prenatal detection may lead to increased parental stress during pregnancy.…”
Section: Discussionmentioning
confidence: 99%